PERKEMBANGAN INDUSTRI E-SPORT DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI DI PEMATANG SIANTAR - Romario F D Purba; Rafael E J Siregar; Pawer D Panjaitan; Darwin Damanik; Ade Nurul Elisyah; Ade Nurma Dani; Rizky Sahertian (MANAJEMEN, 2024)
E-sports is one of the techno-based sports that is generally held in the form of a video game tournament between several players which also has a fan base of millions of people. E-sports has values in the form of sports, economic, social, achievement, and knowledge values like sports in general. The parent organization of E-sport Indonesia itself is the Indonesian E-sport Executive Board (PBESI) chaired by Prof. Dr. Budi Gunawan, S.H., Si. This research aims to find out how the development of E-sport and what impact it has on economic growth in Pematangsiantar City.